2020
DOI: 10.1039/d0dt01790f
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of the synthesis of thorite (ThSiO4) under environmental representative conditions

Abstract: Thorite, (ThSiO4 ) with Zircon type structure, is one of the most abundant natural sources of thorium on earth. Generally, actinides are known to form nanoparticles in silicate medium, though...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This could cause the dissolution of another ceramic waste form and allow for the formation of an actinide orthosilicate, with such hypothetical conditions being similar to those used in synthesizing PuSiO 4 . These actinide orthosilicate could be formed first as colloids, which could impact the actinide mobility and allow their transport over important distances. Thus, here we consider the possible tetravalent states of these heavy transuranic elements and their potential impact on the structural stability.…”
Section: Resultsmentioning
confidence: 99%
“…This could cause the dissolution of another ceramic waste form and allow for the formation of an actinide orthosilicate, with such hypothetical conditions being similar to those used in synthesizing PuSiO 4 . These actinide orthosilicate could be formed first as colloids, which could impact the actinide mobility and allow their transport over important distances. Thus, here we consider the possible tetravalent states of these heavy transuranic elements and their potential impact on the structural stability.…”
Section: Resultsmentioning
confidence: 99%
“…Even if the formation of plutonium silicate complexes and solid plutonium silicate species (or that of other actinide or surrogate elements) has been reported, [5][6][7][8][9][10][11][12] plutonium (IV) chemistry in silicate environment remains poorly understood. Among them, Pu(OSi(OH) 3 ) 3+ was prepared between pH 0.3 and 1.4 in diluted aqueous plutonium and silicate solution and a log(β°) = 11.8 (1) value was evaluated according to equation (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, if the redox environment becomes strongly oxidative, a transformation from trivalent actinide silicates to the tetravalent actinide orthosilicate may occur driven by thermodynamics, such as that demonstrated in the case of A-Ce 2 Si 2 O 7 → CeSiO 4 or Ce 4.67 (SiO 4 ) 3 O → CeSiO 4 . Finally, as actinides are known to form nanoparticles in reactive silicate rich fluids, it could enable the actinide silicate complexes or compounds to be transported in colloidal forms immense distances away from a breached canister if the particles would not settle. , …”
Section: Discussionmentioning
confidence: 99%
“…Radionuclides, especially actinides (An), when leaked from the multibarrier systems may interact with silicate-rich fluids. They could potentially form An-silicate colloids, solid particles, ,, or An-silicate aqueous complexes , under either hydrothermal conditions presented in the early stages of the repository or ambient conditions in either the late stages of the repository or down the hydrogeological gradient. Such concerns are further justified as it has been previously demonstrated that Pu and other actinides can be transported on immense distances in the colloidal forms. …”
Section: Introductionmentioning
confidence: 99%